Perencanaan Investasi Fasilitas Gudang Tambang Pasir Berdasarkan Analisis Struktur Biaya Dan Evaluasi Kelayakan Finansial Menggunakan Metode Benefit Cost Ratio (BCR) - Cholby Efendy; Amri Gunasti (Journal of Science and Engineering, 2026)
This stu The establishment of a sand mining storage facility requires careful engineering and economic planning to ensure long-term structural durability and finansial efficiency. This study evaluates the investment planning for a sand mining warehouse by analyzing its cost structure and financial feasibility using the Benefit-Cost Ratio (BCR) method. High-volume bulk materials like sand exert significant lateral and vertical loads, necessitating robust reinforced concrete design and optimal material selection. Financial data were analyzed over a 10-year planning horizon with an assumed discount rate of 10% per annum. The initial capital expenditure (CapEx) includes land acquisition, earthworks, and structural concrete construction, while operational expenditure (OpEx) covers maintenance and logistical management. The cash flow simulation integrates projected annual revenues from enhanced logistics and reduced material degradation. The structural analysis ensures that the facility complies with Indonesian concrete standards to prevent failure under peak load configurations. The financial evaluation yields a BCR value greater than 1.0, indicating that the discounted benefits outweigh the total capitalized costs. This comprehensive approach proves that integrating structural integrity with rigorous financial parameters provides a reliable framework for industrial infrastructure investment, minimizing economic risks while maximizing structural service life.